Hormonal and Nutritional Features in Contrasting Rootstock-mediated Tomato Growth under Low-phosphorus Nutrition - Martínez-Andújar, Cristina; Ruiz-Lozano, Juan M.; Dodd, Ian C.; Albacete, Alfonso; Pérez-Alfocea, Francisco (Frontiers in Plant Science, 2017)
Grafting provides a tool aimed to increase low P stress tolerance of crops, however little is known about the mechanism (s) by which rootstocks can confer resistance to P deprivation. In this study, 4 contrasting groups of rootstocks from different genetic backgrounds (Solanum lycopersicum var. cerasiforme and introgression and recombinant inbred lines derived from the wild relatives S. pennellii and S. pimpinellifolium) were grafted to a commercial F1 hybrid scion and cultivated under control (1 mM, c) and P deficient (0.1 mM, p) conditions for 30 days, to analyse rootstocks-mediated traits that impart low (L, low shoot dry weight) or high (H, high shoot dry weight) vigour. Xylem sap ionic and hormonal anlyses leaf nutritional status suggested that some physiological traits can explain rootstocks impacts on shoot growth. Although xylem P concentration increased with root biomass under both growing conditions, shoot biomass under low-P was explained by neither changes in root growth nor P transport and assimilation. Indeed, decreased root P export only explained the sensitivity of the HcLp rootstocks, while leaf P status was similarly affected in all graft combinations. Interestingly, most of the nutrients analysed in the xylem sap correlated with root biomass under standard fertilization but only Ca was consistently related to shoot biomass under both control and low-P, suggesting an important role for this nutrient in rootstock-mediated vigour. Moreover, foliar Ca, S and Mn concentrations were (i) specifically correlated with shoot growth under low-P and (ii) positively and negatively associated to the root-to-shoot transport of the cytokinin trans-zeatin (t-Z) and the ethylene precursor 1-aminocyclopropane-1-carboxylic acid (ACC), respectively. Indeed, those hormones seem to play an antagonistic positive (t-Z) and negative (ACC) role in the rootstock-mediated regulation of shoot growth in response to P nutrition. The use of Hp-type rootstocks seems to enhance P use efficiency of a commercial scion variety, therefore could potentially be used for increasing yield and agronomic stability under low P availability.